Stochastic education in childhood: Examining the learning of teachers and students - de Souza, Antonio Carlos [UNESP]; Lopes, Celi Espasandin; de Oliveira, Débora (My University, 2014)
This paper presents discussions on stochastic education in early childhood, based on two doctoral research projects carried out with groups of preschool teachers from public schools in the Brazilian cities of Suzano and São Paulo who were participating in a continuing education program. The objective is to reflect on the analysis of two didactic situations related to the learning of statistics in mathematics classes. The results show evidence of the mathematics learning of the teachers who teach mathematics in early childhood. They also highlight the mathematical and statistical relations that children are able to establish when carrying out stochastic activities included in their childhood context.
Keywords: Early childhood education; Statistics education research; Stochastics; Teacher education